Práticas cotidianas do serviço de atendimento móvel de urgência - Meiriele Tavares Araujo (2013)
SAMU is a component of pre-hospital care that it is rising and growing in Brazil. It happen because it is necessary to minimize deaths and sequelae as a result of inadequate emergencies care in extra-hospital environment. This service has particularities and minutiae in internaland external work. These actual services as well as their relations with other health services in the health network are considered as not traditional services. This qualitative research are based on the theoretical framework post-structuralism seeks to analyze the hegemonic discourses embodied in the daily practices of SAMU professionals´ in Belo Horizonte, Minas Gerais states, Brazil, in order to configure the relations of visibility and recognition. As methodological and analytical resource was employed a critical discourse analysis in semistructuredinterviews with professionals from different categories in the service, in order to describ how the discourses present in everyday life happen. Be found in Everyday Practice the presence of hegemonic discourses that legitimize the dominance relationships in service as well as the key role of human and non-human actors in perpetuating these dominancerelationships, contributing to the maintenance of truth discourses, control and supervision of professionals and their performances. Other points highlighted were the ambivalence between the discourses of visibility and recognition, since not always be visible is to be socially recognized. This visibility has exchanges with the classification of subjects and maintain this in the context of the daily service. The classification behavior can generates pre conceptions about this subject classified. Also regarding visibility is possible to infer that there is symmetry in the visibility and recognition of some professionals and invisibility to others in the SAMU. This study, while it partially fulfilled with the proposed objective, served as a point of arrival in a format different from that service analysis and points to several exit points within a range of possibilities for developments on the other researches about SAMU, practice and daily work, in a more reflective and critical, just trying to overcome the descriptions.